A Rancang Bangun Sistem Pengendali Lampu Jalan Otomatis Berbasis Sensor Cahaya dan Mikrokontroler Arduino: Pengendali Lampu Jalan Otomatis - Wahyu Imam Fauzi Wibisono; Syafaat, Mokhammad; Kasiyanto; Widiatmoko, Dekki; Maulana, Rafi (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2024)
Abstract — To improve energy efficiency and street light operation, this study proposes the design of an automatic street light control system based on a light sensor and Arduino microcontroller. Conventional street lights are often turned on throughout the night without considering the surrounding lighting, leading to energy waste. The proposed system uses a light sensor to detect ambient light intensity and uses data from the sensor to automatically control the street light's on and off state. The research methodology includes the development of both software and hardware components. Light sensors are strategically placed to instantly measure the surrounding light intensity. The Arduino microcontroller is programmed to process data from the light sensor and control a relay connected to the street light. When the light intensity drops below a certain threshold, the microcontroller will activate the street light, and when the light intensity exceeds the predetermined threshold, the light will turn off. This study finds that an automatic street light control system based on a light sensor and Arduino microcontroller is an economical and efficient solution to optimize energy use in street lighting. This system can be widely implemented to support energy-saving programs and smarter, more efficient street lighting infrastructure management. Keywords— Light sensor, Arduino microcontroller, Automatic street light control, Energy efficiency, Street lighting optimization